2021
DOI: 10.21203/rs.3.rs-290044/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The antihyperlipidemic drug Potassium Piperate impairs migration and tumorgenesis of breast cancer cells via upregulation of miR-31

Abstract: Background Breast cancer is a leading malignant tumor which causes deaths among women, and metastasis is the primary cause for mortality in breast cancer. Due to the involvement of many regulatory molecules and signaling pathways, the occurrence and development process of metastasis needs to be further studied. MicroRNAs (miRNAs) are ubiquitously expressed small non-coding RNAs that have been shown to play an important role in the diagnosis and treatment of many diseases, as well as constituting an attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…We demonstrated previously that the transcription of DNA methyltransferase DNMT1 , DNMT3A , DNMT3B , and COQ3 genes were downregulated in GBK-treated MCF-7 cells ( 31 ). In this study, we found that the methylation levels at the CpG of lncRNA LOC554202 decreased significantly under GBK treatment in a dose-dependent manner in breast cancer cell lines ( 45 ). Therefore, GBK treatment affects the epigenetic modification at the CpG sites by downregulating DNA methyltransferases and plays an important role in the upregulation of both the LOC554202 and miR-31 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 69%
“…We demonstrated previously that the transcription of DNA methyltransferase DNMT1 , DNMT3A , DNMT3B , and COQ3 genes were downregulated in GBK-treated MCF-7 cells ( 31 ). In this study, we found that the methylation levels at the CpG of lncRNA LOC554202 decreased significantly under GBK treatment in a dose-dependent manner in breast cancer cell lines ( 45 ). Therefore, GBK treatment affects the epigenetic modification at the CpG sites by downregulating DNA methyltransferases and plays an important role in the upregulation of both the LOC554202 and miR-31 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 69%